THE IMPORTANCE OF EDUCATIONAL ACTIVITIES IN PREPARING CHILDREN FOR SCHOOL (Conferencea, 2024)
This article is about the importance of educational activities in preparing children for school. Educational activities mean informing children of the necessary knowledge and skills by the educator in general. It is said that educational activities are carried out throughout the day.